RUANG EKONOMI BERBASIS AGRIKULTUR DAN PENGOLAHAN AIR KOTOR DENGAN MENGGUNAKAN INSTALASI PENGOLAHAN AIR ALAMI PADA KAMPUNG APUNG - Dewi Nathania Herijanto; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Located in rice fields, Kampung Apung was the same as other villages in that it was on the ground and not floating. However, due to changes in topography, time and urban needs, there has been considerable development into an industrial and warehousing area in the surroundings of the Apung village so that the village becomes hollow and sinks. Changes in the area into industry and warehousing have resulted in the area experiencing a shortage of infiltration areas. The sinking of the village interrupts the daily activities of the residents, disrupts the economy and social life of the residents. Local interventions are presented through Urban Acupuncture using everyday methods and typology. The choice of this method is expected to cure the issue of degradation that occurs in the Kampung Apung. The program presented is in the form of structuring Floating Villages into vertical villages and making creative economic activities in villages with an agricultural base that is equipped with dirty water treatment. It is hoped that the presence of this additional program can increase the economy of the residents of the Kampung Apung so that it can have a positive impact on the Apung village. Keywords:  Economic space; agriculture; natural water treatment plant Abstrak Berada pada lahan persawahan di Kapuk, Jakarta Barat, Kampung Apung awalnya sama seperti kampung lainnya yang berada di atas tanah dan tidak terapung. Tetapi karena perubahan topografi, zaman dan, kebutuhan kota, terjadi pembangunan yang cukup besar menjadi kawasan industri dan pergudangan pada lingkungan sekitar kampung Apung sehingga kampung menjadi cekungan dan tenggelam. Perubahan fungsi kawasan menjadi perindustrian dan pergudangan mengakibatkan kawasan mengalami kekurangan area resapan. Tenggelamnya kampung mengganggu aktivitas keseharian warga, perekonomian, dan sosial warga. Intervensi lokal dihadirkan melalui Urban Acupuncture dengan menggunakan metode keseharian dan tipologi. Pemilihan metode ini diharapkan dapat menyembuhkan isu degradasi yang terjadi pada kampung Apung. Program yang dihadirkan berupa penataan Kampung Apung menjadi kampung vertikal dan pembuatan kegiatan ekonomi kreatif pada kampung dengan basis agrikultur yang dilengkapi dengan pengolahan air kotor. Diharapkan dengan hadirnya program tambahan ini dapat menaikkan perekonomian warga kampung Apung sehingga dapat memberi dampak positif bagi kampung Apung.